Preparation of Navigation Plan for Scenic Routes Between Airports at Bangkok(VTBD) and U-Tapao (VTBU) and Validation using Flight Simulator - Govindan, Mari Prabu (Science & Technology Asia, 2024)
A navigation plan is an integral part of the airline dispatch operations which helps and guides the pilot by providing all of the information needed for the safe flight to reach a destination. It must be framed with the utmost focus to provide the most accurate data and information so that the pilot can follow the scheduled time. There are n- number of possible routes to reach a destination with a flight. In this research, a flight plan for finding the most scenic route between Don Mueang International airport(VTBD) and U Tapao International airport(VTBU) is done along with the simulation of the route with the help of a flight simulator. Here visual flight rules are used to make flight plans for a Cessna 172R aircraft and the navigation plan is completely simulated with redbird 2 flight simulator.